Buprenorphine and major metabolites in blood specimens collected for drug analysis in law enforcement purposes - Oechsler, Stephanie; Skopp, Gisela (Forensic science international, 2010)
A liquid chromatographic/electrospray ionization tandem mass spectrometric method for the quantification of buprenorphine (BUP), norbuprenorphine (NBUP), buprenorphine-3-β-d-glucuronide (BUPG) and norbuprenorphine-3-β-d-glucuronide (NBUPG) in serum samples was developed and validated. Pre-treatment of BUP and NBUP was by liquid-liquid extraction, while glucuronides were favourably isolated by solid phase extraction. Separation in 2 separate runs (2× 5min) was achieved using isocratic elution. The method was applied to 20 authentic serum specimens collected for law enforcement purposes where BUP intake had been indicated. The parent drug was not detectable in half of the specimens at a lower limit of detection of 0.2ng/mL, whereas NBUP could be determined from any sample but one. NBUPG is the major metabolite present, which could be identified along with BUPG in all samples under investigation. In authentic specimens it could be advisable to monitor BUP metabolites along with the parent drug.
Online verfügbar 16 December 2009
Gesehen am 12.06.2023